Maximal swimming distance at anaerobic critical velocity - Louro, Hugo (2021)
The aim of this study was to assess anaerobic critical velocity in swimming, its relationships with short distance performance and determine the maximal distance that can be performed at this assessed velocity. Nine male swimmers performed 15, 25 and 50 m maximal front-crawl swimming (30 min rest intervals) to calculate anaerobic critical velocity. Each swimmer also performed 100 m front-crawl at maximal velocity. Additionally, it was aimed to assess the maximal distance that could be performed at the previously assessed individual anaerobic critical velocity (up to 150 m). Capillary blood lactate concentrations and biomechanical variables were assessed on both swimming tests. Results show that anaerobic critical velocity and maximal 100 m front-crawl were highly correlated (r=0.88, P<0.01) and no differences were noted between them (1.61 ± 0.07 m.s-1 and 1.60 ± 0.08 m.s-1, respectively; P=0.34). The swimmers were able to perform 97.22 ± 20.51 m at anaerobic critical velocity. However, no relationship was found between the total distance achieved and anaerobic critical velocity (r=0.27, P=0.49) and 100m performance (r=0.49, P=0.19). Blood lactate concentration values were also different in the 3rd and 5th minutes of recovery between the two tests (P<0.05). Likewise, variations of the biomechanical variables were noted between the tests. Our results suggest that anaerobic critical velocity is a relevant tool related to the swimmer’s overall performance in short distances events. However, higher assessed velocities are not necessarily correspondent to more swimming distances without fatigue